Law of the sea conference: issues and problems - Hossain, Ishtiaq (1982)
The Third World, led by the Group of 77 and the developed countries led by the United States, are sharply divided over a number of of issues that are threatening the signing of a treaty on the law of the sea. This paper aims at analysing and evaluating those issues now confronting the United Nations Conference on the Law of the Sea (UNCLOS-III). The analysis will make clear tbe stands taken by the industrial and the Third World, countries over the issues. Self-interests of the maritime countries reign supreme over every rule and regulation. This paper will also discuss those interests and analyse their politico'economic implications.